The role of commander Abdelrahman Ben Salem in the Souk Ahras Region through the overseas archives - Belbekkouche, Souad (The International tax journal, 2025)
This paper aims to shed light on one of the key figures who played a significant role in the Souk Ahras region, based on a collection of archival documents obtained from the Archives Nationales d’Outre-Mer (Overseas Archives) in Aix-en-Provence. We seek to trace the trajectory of this figure, who had defected from the French army and joined the Algerian Revolution in the Souk Ahras area (Douar Ouled Dhia). This defection enabled him to establish ties with several Tunisian allies, including Mahjoub Ben Ali, without preventing him from maintaining a relationship with El-Wardi Kettal, as evidenced by correspondence between them. These documents also contain critical information about his command headquarters, located on Tunisian territory approximately 15 km west of Ghardimaou (Ghar Dimaou), alongside the Second Battalion of Souk Ahras—its structure, organization, and his role in confronting the Morice Line. Additionally, the documents highlight several battles in which "Commander Ben Salem" took part in the Souk Ahras region.